Tubercular paraplegia in pregnancy with complete neurological recovery following antitubercular therapy: a case report - Firdaus Fathima; Ambika Patil; Santosh Rathod (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Spinal tuberculosis with paraplegia during pregnancy is rare and is a diagnostic and therapeutic challenge. Pregnancy, being a relatively immunocompromised state, may prompt rapid destruction of the vertebral body, resulting in an acute and profound neurological deficit. A 23-year-old G2P1L1 woman at 19+5 weeks presented with progressive bilateral lower-limb weakness; MRI showed D2 collapse with epidural collection and cord compression. Sputum Ziehl-Neelsen staining confirmed acid-fast bacilli, and first-line HRZE therapy was started. She recovered completely, continued pregnancy to term, and delivered a healthy male neonate by elective caesarean section. This case supports early MRI diagnosis and timely anti-tubercular therapy alone in selected patients with multidisciplinary care and close maternal-fetal monitoring can lead to complete recovery.